Research advances of single-cell RNA sequencing in kidney - Wang Xin-yao; Deng Zhen-ling; Wang Yue (Linchuang shenzangbing zazhi)
Composed of multiple cell types,kidney is an organ with highly complex structures and functions.Thus it is quite important to clarify the gene transcription map and changes of various types and subtypes of cells under physiological and pathological conditions to elucidate the structure,function and pathogenesis of the diseases.The development of single-cell RNA sequencing has triggered a shift in transcriptomic researches from analyzing the average level of gene transcription in various tissues to transcribing single-cell genes in specific organs（or tissues）at the cellular level.Based upon the elaboration of scRNA-seq technology and the newly discovered subtypes and functions of kidney cells,this review focused upon research advances of scRNA-seq of immune cells in kidney tissues of common kidney diseases.